AI transforming Healthcare Management during Covid-19 pandemic - Efthymiou, Iris-Panagiota; Sidiropoulos, Symeon; Kritas, Dimitrios; Rapti, Paraskevi; Vozikis, Athanassios; Souliotis, Kyriakos (HAPSc Policy Briefs Series, 2020)
The dawn of artificial intelligence (AI) as a platform for improved health care provides unparalleled opportunity to enhance patient and clinical team performance, minimize costs, and reduce the health effects of the community. It provides a broad description of the legal and legislative context of the AI tools intended for the implementation of health care; highlights the need for equality, accessibility, the need for a human rights goal for the work; and identifies important factors for further advancement. AI framework describes the obstacles, drawbacks, and best practices for AI development, adoption, and management. It brings in a paradigm shift to healthcare, driven by rising clinical data access and rapid advancement in analytical techniques. Artificial Intelligence (AI) is going to revolutionize the practice of medicine and change the delivery of healthcare. This paper discusses the role of artificial intelligence in the advancement of health care and associated fields. It also discusses, the value of artificial intelligence in various healthcare sectors’ transformation.